1973
DOI: 10.1203/00006450-197303000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Estradiol-17, β on the Magnitude and Distribution of Uterine Blood Flow in Nonpregnant, Oophorectomized Ewes

Abstract: ExtractIn seven nonpregnant sheep studied either acutely or chronically there was an increase in total uterine blood flow after the systemic, 2-min infusion of 1.0 /xg/kg of estradiol-17, /?. The mean control flow was 20 ± 3 ml/min and the mean flow, measured approximately 2 hr after estradiol, was 283 db 50 ml/min (P < 0.001). The chronic preparations showed a mean increase in flow that was 186 ml/min greater than that measured in the acute preparations. The blood flow to all uterine tissues increased markedl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
45
1
4

Year Published

1977
1977
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(53 citation statements)
references
References 10 publications
3
45
1
4
Order By: Relevance
“…The fact that blood flow through the uterus increases after oestrogen injection has been previously observed for sheep Rosenfeld et al, 1973 ; Abrams & Sharp, 1977). In conscious ovariectomized sheep, a maximal effect on uterine blood flow was observed with a dose of 0-5 µg oestradiol-17ß/kg intra-arterially, and this occurred at 2 h; the effect was still observable 12 h after injection.…”
Section: Discussionmentioning
confidence: 72%
“…The fact that blood flow through the uterus increases after oestrogen injection has been previously observed for sheep Rosenfeld et al, 1973 ; Abrams & Sharp, 1977). In conscious ovariectomized sheep, a maximal effect on uterine blood flow was observed with a dose of 0-5 µg oestradiol-17ß/kg intra-arterially, and this occurred at 2 h; the effect was still observable 12 h after injection.…”
Section: Discussionmentioning
confidence: 72%
“…DISCUSSION It has not been clear whether the changes in uterine blood flow produced by infused angiotensin TI in various species were reflective of uterine vasoconstriction or vasodilation. Part of this dilemma could have resulted from the use of animals studied during the stress of surgery and anesthesia as pointed out specifically with regard to angiotensin II by Assali et al (14) and other vasoactive compounds by Killam et al (15) and Rosenfeld et al (16). However, in studies using chronically instrumented pregnant ewes remote from surgery, we (13) and Lieb et al (20) (Fig.…”
mentioning
confidence: 66%
“…Body weight remained constant or increased. The animals were studied only after they were considered to have recovered from surgical trauma and anesthesia, as evidenced by a normal response of uterine blood flow to 1 ,ug/kg of intravenous 17,8-estradiol (15,16).…”
mentioning
confidence: 99%
“…Therefore, it was our purpose to ascertain in the present investigation whether the chronically instrumented, unanesthetized ewe might serve as an animal model in which systemic and uterine vascular responses could be studied simultaneously. We previously reported that the uteroplacental and other vascular responses to systemic infusions of 17f3-estradiol in nonpregnant sheep are blunted significantly when the animal is under the influence of anesthesia or surgical stress, and that a normal response may not be seen for 4-5 d thereafter (12,19). Assali et al (20) have also reported that in anesthetized sheep the uterine response to bolus infusions of AII is quite different from that found in unanesthetized animals.…”
Section: Resultsmentioning
confidence: 93%
“…Thus, it is preferable to use unanesthetized, unstressed animals remote from surgery to study the responses of the cardiovascular system (in particular the uteroplacental circulation) to vasoactive compounds. This has been addressed in the present investigation by the use of pregnant and nonpregnant ewes remote from surgery or anesthesia that were shown to be in an unstressed, normal physiologic state as determined by an adequate uterine-blood-flow response to an infusion of 17,8-estradiol (12,14,19) and a mean arterial pressure within the normal range (21).…”
Section: Resultsmentioning
confidence: 99%